Organizational Trends in Educational and Professional Adaptation of Foreign Students in the Russian Higher School - T. G. Arkadyeva; S. S. Vladimirova; N. S. Fedotova (Russian State Vocational Pedagogical University, 2015)
The paper looks at the notion of «educational professional adaptation» and defines the relating difficulties facing foreign students in Russian higher school. The attitude of the given category of students to university is indicated along with the first priority tasks for the staff teaching Russian as the second language, the possible ways of fulfilling the above tasks being proposed. The organizational trends in educational professional adaptation of foreign students in Russian higher school are described aiming for their active communication in foreign (Russian) language and increasing motivation for academic and extra- curricular activity.The research methods involve analysis of psycho-pedagogical data related to the research subject, surveying, monitoring and empirical data processing.